Changes in Bioactive Compounds, Antioxidant Activity, and Nutritional Quality of Blood Orange Cultivars at Different Storage Temperatures - Fariborz Habibi; Asghar Ramezanian; Fabián Guillén; Salvador Castillo; María Serrano; Daniel Valero (MDPI AG, 2020)
Information about the postharvest physiological behavior of blood orange cultivars can provide comprehensive insight into the best period of storage to maintain the highest fruit quality during prolonged cold storage. In this paper, changes in nutritional quality, bioactive compounds, and antioxidant enzymes in the juice of four blood orange cultivars ("Moro", "Tarocco", "Sanguinello", and "Sanguine") stored at 2 and 5 °C were studied. Parameters were measured after 0, 30, 60, 90, 120, 150, and 180 days, plus 2 days at 20 °C for shelf life. Sucrose was the sugar found in higher concentrations and decreased during storage in all cultivars, as did glucose and fructose. Organic acids decreased at both temperatures, with the highest content found in "Sanguinello", especially major (citric acid) and ascorbic acid. Total phenolics content (TPC), total anthocyanins (TAC), and individual cyanidin 3-glucoside and cyanidin 3-(6"-malonylglucoside) increased for all cultivars, with "Sanguinello" having higher concentrations. The antioxidant enzymes catalase (CAT), ascorbate peroxidase (APX), and superoxide dismutase (SOD) were also higher in "Sanguinello" and increased during storage. Overall, these results together with the sensory analysis suggested that "Sanguinello" would be the best cultivar for prolonged storage. The results of this study could be useful to select the best storage duration and temperature for each cultivar and provide the presence of such a high-value commodity for fresh consumption or juice processing long after the harvest season.